Answer :

Since, if a = b = c a = b & b = c

Thus, we have



and


Lets simplify these equations. We can rewrite them,



3(x + y – 8) = 2(x + 2y – 14)


3x + 3y – 24 = 2x + 4y – 28


3x – 2x + 3y – 4y = - 28 + 24


x – y = - 4 …(i)



3(3x + y – 12) = 11(x + 2y – 14)


9x + 3y – 36 = 11x + 22y – 154


11x – 9x + 22y – 3y = 154 – 36


2x + 19y = 118 …(ii)


To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.


Lets multiply eq.(i) by 19, so that variable y in both the equations have same coefficient.


Recalling equations (i) & (ii),


x – y = - 4 [×19


2x + 19y = 118



21x = 42


x = 2


Substitute x = 2 in eq.(i)/eq.(ii), as per convenience of solving.


Thus, substituting in eq.(i), we get


2 – y = - 4


y = 2 + 4


y = 6


Hence, we have x = 2 and y = 6


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics